Genetic Diversity of Peach (Prunus persica) Accessions Collected in Northern Vietnam Using ISSR Markers - Dinh Ha Tran; Thanh Huyen Dao; Xuan Binh Ngo; Van Hong Nguyen; Thanh Van Dao; Tien Dung Nguyen (Diversity)
Peach (Prunus persica) is a temperate fruit crop that is widely cultivated in the northern region of Vietnam. This study investigated the genetic diversity of 59 peach accessions collected from northern mountainous provinces in Vietnam using ISSR (inter-simple sequence repeat) markers. The obtained results enabled the evaluation of genetic variation and relationships among peach varieties, which supports breeding programs and germplasm conservation. The analysis identified high levels of polymorphism (92.5%) across six ISSR primers. The accessions were grouped into two main clusters based on a genetic similarity coefficient threshold of 0.674. There were no significant correlations between genetic and geographic distances. The findings underscore the importance of molecular markers like ISSR for identifying genetic relationships and conserving germplasm resources. The results also highlight the potential genetic drift resulting from the trading and exchange of peach varieties among farmers, leading to the creation of regionally named varieties. This study provides valuable insights into the genetic diversity of Vietnamese peaches, supporting efforts to preserve and utilize these resources for breeding and agricultural development.